Proceedings of the Second (2015) ACM Conference on Learning @ Scale 2015
DOI: 10.1145/2724660.2724680
|View full text |Cite
|
Sign up to set email alerts
|

Attrition and Achievement Gaps in Online Learning

Abstract: Attrition in online learning is generally higher than in traditional settings, especially in large-scale online learning environments. A systematic analysis of individual differences in attrition and performance in 20 massive open online courses (N > 67, 000) revealed a geographic achievement gap and a gender achievement gap. Online learners in Africa, Asia, and Latin America scored substantially lower grades and were only half as likely to persist than those in Europe, Oceania, and Northern America. Women als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
4
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(197 citation statements)
references
References 18 publications
9
173
4
11
Order By: Relevance
“…In MOOCs, where the population of learners is heterogeneous and people register with different intentions, motivation plays a key role on how learners will address the course (Kizilcec & Halawa, 2015;Hood, Littlejohn, & Milligan, 2015). However, in MOOCs, unlike in other types of online courses, learners' intrinsic motivation for the subject addressed is of higher importance, as the certification obtained after completion (extrinsic motivation) has typically a low recognition (Wang & Baker, 2015).…”
Section: Motivation In Moocsmentioning
confidence: 99%
See 1 more Smart Citation
“…In MOOCs, where the population of learners is heterogeneous and people register with different intentions, motivation plays a key role on how learners will address the course (Kizilcec & Halawa, 2015;Hood, Littlejohn, & Milligan, 2015). However, in MOOCs, unlike in other types of online courses, learners' intrinsic motivation for the subject addressed is of higher importance, as the certification obtained after completion (extrinsic motivation) has typically a low recognition (Wang & Baker, 2015).…”
Section: Motivation In Moocsmentioning
confidence: 99%
“…Time management is a specific, self-regulated learning skill that includes scheduling, planning, and managing the personal study time. Studies reveal that poor time management is one of the main reasons for withdrawing from MOOC, along with the lack of attractiveness and suitability of the course for each learner (Nawrot & Doucet 2014;Kizilcec & Halawa, 2015;Zheng, Rosson, Shih, & Carroll, 2015). Furthermore, in a recent article by Kizilcec, Pérez-Sanagustín, and Maldonado (2016) in which the authors interviewed 17 learners who successfully completed a MOOC, time management strategies, such as reserving time in the week for studying, were identified as some of the most effective self-regulation learning strategies.…”
Section: Self-regulated Learning Strategies In Moocsmentioning
confidence: 99%
“…Coding bootcamps can be expensive, require a significant time investment and are located primarily in technology corridors and urban settings. And achievement gaps remain; in a 2015 study 10 of more than 67,000 MOOC students, two Stanford researchers found that female students and students of both genders from Africa, Asia and Latin America were less likely to reach certain course milestones -such as watching more than 50% of the lectures -and earned lower grades than male students and MOOC students from North America, Europe and Oceania.…”
Section: Source: Ilabour (Http://gonaturecom/2gze5tz)mentioning
confidence: 99%
“…Third, the reputation of online learning in general and persistent learning traditions. Studies show that attrition is much higher in online classes than in traditional classroom settings (Kizilcec et al, 2015) and that learners in Africa, Latin America and Asia were up to 50% less likely to persist with lectures and achieve grade milestones than learners from North America, Europe and Oceania (p. 5). In the case of Ecuador, a traditionally authority-orientated learning tradition makes it difficult for newer approaches to be accepted.…”
Section: Problems and Conclusionmentioning
confidence: 99%
“…On the other hand, learners with less learning facility, underperform easily if not supported by the tutor, meaning a one-to-one situation. The novelty of online language classes in Ecuador and authoritarian learning traditions mean that an online class in Ecuador must be -to guarantee a learning process -in a small and personalized class with the possibility of individual tutoring instead of MOOCs (Massive Open Online Courses) where learners find themselves often unable to cope (Kizilcec et al, 2015). Fourth, the institutional background and sustainability knowledge.…”
Section: Problems and Conclusionmentioning
confidence: 99%